Synthesis, Characterization and Photobiological Studies of Ru(II) Dyads Derived from α‐Oligothiophene Derivatives of 1, 10‐Phenanthroline1. (27th October 2018) - Monro, Susan; Cameron, Colin G.; Zhu, Xiaolin; Colón, Katsuya L.; Yin, Huimin; Sainuddin, Tariq; Hetu, Marc; Pinto, Mitch; Fuller, Anderson; Bennett, Leah; Roque, John; Sun, Wenfang; et al.
Abstract: Three new bis(2, 2′‐bipyridine)‐heteroleptic Ru(II) dyads incorporating thienyl groups ( n = 1–3, compounds 1, 2 and 3, respectively) appended to 1, 10‐phenanthroline were synthesized and characterized to investigate the impact of n on the photophysical and photobiological properties within the series. All three complexes showed unstructured emission near 618 nm from a triplet metal‐to‐ligand charge transfer ( 3 MLCT) state with a lifetime ( τ em ) of approximately 1 μs. Transient absorption measurements revealed an additional excited state that was nonemissive and long‐lived ( τ TA = 43 μs for 2 and 27 μs for 3), assigned as a triplet intraligand ( 3 IL) state that was accessible only in 2 and 3. All three complexes were strong singlet oxygen ( 1 O2 ) sensitizers, with quantum yields ( Φ ∆ ) for 2 and 3 being the largest (74–78%), and all three were photocytotoxic to cancer cells with visible light activation in the order: 3 > 2 > 1. Cell‐free DNA photodamage followed the same trend, where potency increased with decreasing 3 IL energy. Compounds 2 and 3 also showed in vitro photobiological effects with red light (625 nm), where their molar absorptivities were <100 m −1 cm −1 . These findings highlight that Ru(II) dyads derived from α ‐oligothiophenes directly appended to 1, 10‐phenanthroline—namely 2 and 3—possess low‐lying 3 IL states that are highly photosensitizing, and they may therefore be of interest for photobiological applications such as photodynamic therapy (PDT). Abstract : Ru(II) dyads derived from imidazo[4, 5‐ f ][1, 10]phenanthroline ligands appended with α ‐oligothienyl groups were investigated for their photophysical and photobiological properties. The compounds differed systematically by the number of thienyl groups, where n = 1–3 in1-3, respectively. All three compounds were effective singlet oxygen generators and were phototoxic to cells with visible light, with potency positively correlated to n . Compounds2 and3 were characterized by low‐lying intraligand triplet excited states with prolonged lifetimes that give rise to in vitro phototoxic effects with red light, where molar extinction coefficients were vanishingly small.